Lithium Preparations in Psychiatry, Addiction Medicine and Neurology (To the 70th Anniversary of John Cade’s Discovery). Part I. History - Roman A. Bekker; Yuriy V. Bykov (Acta Biomedica Scientifica, 2019)
The use of lithium salts in psychiatry has a long, more than two-thousand-year history. It goes back to the ideas of Hippocrates II, Galen and Soran of Ephesus regarding the feasibility of using mineral waters from certain sources, which, as we know today, were rich in lithium, magnesium and bromine salts, for the treatment of both manic and depressive states. Later, this effect of lithium salts was rediscovered – independently of each other – in the mid-19th century by the American psychiatrist William Alexander Hammond and the Danish psychiatrist Carl Lange. However, since this discovery was based on incorrect premises, namely, on the theory of «brain urine acid diathesis» as the cause of mental illness, it was not accepted, ignored and even ridiculed by colleagues. The rediscovery of the anti-manic effect of lithium salts by John Cade in 1948 is one of the greatest discoveries of psychiatry of the 20th century.The mechanisms of lithium therapeutic action are complex, diverse and not fully understood to this day. Initially, John Cade suggested that this effect of lithium is associated with its deficiency in patients with bipolar disorder and that exogenous lithium aids in compensation of such deficiency, or that patients with bipolar disorder suffer from some congenital disorder of lithium metabolism, thus requiring higher daily lithium doses than healthy people. However, it was soon shown that this was not the case.Despite the emergence of a significant number of alternative mood stabilizers, lithium remains relevant in psychiatry to this day.